A brief tale of the two faces of narcissism and the two facets of pride. (1st May 2018) - Rogoza, Radosław; Kwiatkowska, Maria Magdalena; Kowalski, Christopher Marcin; Ślaski, Sławomir
Abstract: Existing research suggests that narcissism is moderately associated with authentic pride and weakly associated with hubristic pride. In the current paper, we investigate whether the differentiation of the two faces of narcissism (i.e., admiration and rivalry), provides an alternate account of the relationships between these variables. We hypothesised that such differentiation would result in a contradictory pattern of relations with authentic pride, whilst both narcissistic strategies would be positively correlated with hubristic pride. The study was conducted on an adult sample using the Authentic and Hubristic Pride Scale and Narcissistic Admiration and Rivalry Questionnaire. The hypotheses were tested using a structural equation model, which was well fitted to the data. The results supported our expectations regarding the mutual suppression effect of the two faces of narcissism on the relation with authentic pride as well as the common direction of the relations with the hubristic pride. Highlights: Admiration positively predicts authentic pride. Rivalry negatively predicts authentic pride. Admiration and rivalry positively predict hubristic pride. Narcissism may be functional to some extent despite being malevolent personality trait.